A Critical Appraisal of Functionalized 2-Dimensional Carbon-Based Nanomaterials for Drug Delivery Applications - Singh, Dilpreet; Gupta, G.D.; Gupta, Nimish; Verma, Princi; Dey, Abhisek; Kaur, Simranjeet; Kumar, Akshay; Raj, Namandeep (Recent Patents on Nanotechnology, 2024)
The development of an efficient and innovative drug delivery system is essential to improve the pharmacological parameters of the medicinal compound or drug. The technique or manner used to improve the pharmacological parameters plays a crucial role in the delivery system. In the current scenario, various drug delivery systems are available where nanotechnology has firmly established itself in the field of drug delivery. One of the most prevalent elements is carbon with its allotropic modifications such as graphene-based nanomaterials, carbon nanotubes, carbon dots, and carbon fullerenes, these nanomaterials offer notable physiochemical and biochemical properties for the delivery applications due to their smaller size, surface area, and ability to interact with the cells or tissues. The exceptional physicochemical properties of carbon-based 2D nanomaterials, such as graphene and carbon nanotubes, make them attractive candidates for drug delivery systems. These nanomaterials offer a large surface area, high drug loading capacity, and tunable surface chemistry, enabling efficient encapsulation, controlled release, and targeted delivery of therapeutic agents. These properties of the nanomaterials can be exploited for drug delivery applications, like assisting the target delivery of drugs and aiding combination molecular imaging. This review emphasizes on the recent patents on 2D carbon-based nanomaterial and their role in drug delivery systems. Carbon-based 2D nanomaterials present a wealth of opportunities for advanced drug delivery systems. Their exceptional properties and versatility offers great potential in improving therapeutic efficacy, minimizing side effects, and enabling personalized medicine and the recent patents on 2D nanomaterial.
Keywords: graphene nanostructures